Corporations' choice of tax regime when transition costs are small and income shifting potential is large - Annette Alstadsæter; Knut Reidar Wangen (Center for Economic Studies and ifo Institute (CESifo), 2008)
The literature provides ambiguous results on the effect of taxes on businesses' choice of organizational form, partly due to a lack of good firm-level data. Our micro data covers the full population of non-financial Norwegian corporations over ten years. During this period, the dual income tax system allowed corporations to shift tax regime without changing organizational form. We show that the income shifting potential is large for the active owners of a corporation that participate in a tax reducing coalition. Our results show that corporations respond to tax incentives and change tax regime in order to reduce tax payments. But persistent cohort effects in the choice of tax regime and substantial unobserved corporation-specific effects indicate that non-tax factors matter as well. Corporations founded prior to the introduction of the dual income tax differ substantially from those founded after in their adaptation to the incentives for shifting tax regime.
Keywords: D21; H25; H3; 330; Corporate taxation; choice of tax regime; tax minimization; Unternehmensbesteuerung; Steuerplanung; Steuerreform; Duale Einkommensteuer; Rechtsformwahl; Norwegen